Indigenous Peacebuilding - Omona, David Andrew (The Palgrave encyclopedia of global security studies, 2020)
Conflict, “the pursuit of incompatible goals by different groups” (Miall et al. 2005, p. 22), has been part of humanity from antiquity. Given its destructive nature, every human society has an imbued mechanism to address conflicts using principles and practices central to the support of reconciliation and amnesty.
Keywords: Conflict · Indigenous · Peacebuilding